Difficulties of Young Adults With Dyslexia in Reading and Writing Numbers. (July 2022) - Cornoldi, Cesare; Rivella, Carlotta; Montesano, Lorena; Toffalini, Enrico
Letters and numbers are different domains, and their differentiation increases with schooling. It has nonetheless been argued that reading alphabetic and numerical materials partly involves the same processes, even in adults. Whether individuals with dyslexia have difficulty reading and writing numbers remains to be established. This study examined this issue in a group of 30 young adults with a diagnosis of dyslexia, without any concurrent specific difficulty in processing quantities, compared with a typically developing group matched for gender, age, university attended and course of studies, and approximate calculation ability. The results showed that adults with dyslexia also have severe difficulty in reading and writing numbers. It emerged that their number reading speed correlated moderately with word reading speed. We concluded that dyslexia is specifically related with difficulties in reading and writing not only alphabetic material but also numerical material. Our findings suggest that these abilities should be considered more carefully when assessing and supporting individuals with dyslexia.